PENGARUH RASIO LEVERAGE, RASIO PROFITABILITAS, RASIO AKTIVITAS, RASIO LIKUIDITAS, DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2016 - Duma Rahel Situmorang (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2018)
The purpose of the study is to determine the effect of leverage ratio, profitability ratio, activity ratio, liquidity ratio, and sales growth on financial distress of manufactured companies listed on the Indonesia Stock Exchange. This research is a causal associative research type with the study population is manufactured companies listed on the Indonesia Stock Exchange (IDX) in 2013 - 2016, amounting to 165 companies. The sample selection is done by purposive sampling in order to obtain 15 companies that become research samples. The type of data used is secondary data with data collection using documentation and literature study methods. The data analysis technique used is multiple linear regression analysis. The result of this study shows that partially, liquidity ratio, profitability ratio, leverage ratio and activity ratio has had significant influence on financial distress. Meanwhile, sales growth not significant influence on financial distress. While simultaneously, all of independent variable had significant influence on financial distress on manufactured companies listed on the Indonesia Stock Exchange.